The Effect of Social Media Use on Students' Scientific Writing Ability - eko prasetiyo (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
This article aims to analyze the effect of social media use on students' ability to write scientific papers in an educational environment, especially at the Ngawi Institute of Islamic Religion. Quantitative methods are used to obtain objective and numerically measurable results. By using the regression test and the coefficient of determination, the results show that the use of social media has a significant impact on the ability to write scientific papers of students, with a calculated t value of 6.128, which is greater than the t value of 1.195 with a significance of 0.00 <0.05. from this value, social media has a positive and significant influence on student's ability to write scientific papers and an R-value of 0.150. From this output, the coefficient of determination (R Square) is 0.053. The coefficient of determination means that the effect of the independent variable (social media) on the dependent variable (ability to write scientific papers) is 5.3%. This research article is expected to provide insights for educational institutions in designing policies and strategies that support student learning in the digital era and provide practical guidance for students in managing time and using social media wisely.